2011
DOI: 10.1177/0022146511418236
|View full text |Cite
|
Sign up to set email alerts
|

Race-Ethnicity and Medical Services for Infertility

Abstract: Evidence of group differences in reproductive control and access to reproductive health care suggests the continued existence of "stratified reproduction" in the United States. Women of color are overrepresented among people with infertility but are underrepresented among those who receive medical services. The authors employ path analysis to uncover mechanisms accounting for these differences among black, Hispanic, Asian, and non-Hispanic white women using a probability-based sample of 2,162 U.S. women. Black… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(44 citation statements)
references
References 44 publications
(58 reference statements)
2
40
0
Order By: Relevance
“…Not surprisingly, having financial means, insurance coverage, and connection with the medical system (recent physical exam) were all predictive of reporting a medical evaluation for infertility in our cohort. We did not find significant differences between race and marital status and fertility evaluation, which have been reported previously (5, 7, 11, 14, 26). This may be a reflection of our highly educated, relatively homogenous population among which there may be limited power to detect such differences (n black women=68) or this may support previous work in which, after adjustment, the effect of race was attenuated by other socio-economic factors (9, 15).…”
Section: Discussionsupporting
confidence: 76%
“…Not surprisingly, having financial means, insurance coverage, and connection with the medical system (recent physical exam) were all predictive of reporting a medical evaluation for infertility in our cohort. We did not find significant differences between race and marital status and fertility evaluation, which have been reported previously (5, 7, 11, 14, 26). This may be a reflection of our highly educated, relatively homogenous population among which there may be limited power to detect such differences (n black women=68) or this may support previous work in which, after adjustment, the effect of race was attenuated by other socio-economic factors (9, 15).…”
Section: Discussionsupporting
confidence: 76%
“…Previous analyses have shown that women who make use of medical help for infertility tend to be a highly select group, which may reflect the fact that women of lower socioeconomic status are less likely to have adequate health insurance coverage and other financial resources to afford the necessary diagnostic or treatment services (4, 5, 6, 7, 8, 9, 10). We anticipate that women who utilize ART are an even more select group given the expense and duration of treatment, and limited insurance coverage for ART.…”
mentioning
confidence: 99%
“…A cohort of immigrant Latinos also reported that cost, education, communication, difficulty navigating hospital and insurance systems, and poor physician care prevented them from accessing infertility treatments [8]. African American and Hispanic women were less likely than white women to have money or private insurance to help cover the costs of infertility treatments [9]. They also reported having difficulties finding a physician, taking time off of work, and paying for infertility treatments [26].…”
Section: Infertility Treatment and Race/ethnicitymentioning
confidence: 99%
“…Even with coverage, the associated cost of ART remains high for many [2, 4, 5]. Recent literature has revealed that of the infertile women who are unable to pay for treatments, a large proportion are non-white and must deal with racial prejudices, high cost of treatment with low income, lack of understanding of medical terminology and procedures, and additional cultural expectations and stigmas [59]. Out of the infertile minority patient population in the United States, refugees and asylum seekers have even more difficulty accessing infertility care due to even larger language and cultural barriers, traumatic histories, and difficulty applying for cost support grants before they can be approved for permanent United States residence [10].…”
Section: Introductionmentioning
confidence: 99%